Variable Factors Determining Purchasing Intention of the Toyota-Branded Innova Zenix Hev Car at Dealership Jakarta, Indonesia - Emsa Adiyati; Thamrin Abdullah; Jubery Marwan (Journal of Center for Energy Policy and Human Resources Capacity Development, 2025)
The purpose of this research is to examine and investigate the factors that determine the level of interest in purchasing the Toyota-branded Innova Zenix HEV model that is available at dealerships in Jakarta, Indonesia. For the purpose of the study, primary data were obtained using an explanatory research design with a quantitative approach. These data had been evaluated for validity, reliability, and homogeneity, and saturated sampling was used to the complete population. A factor analysis was performed on the data in order to determine which components had the most impact. Product quality, pricing, service and network availability, and credit financing are the primary factors that determine interest in making a purchase, according to the findings. On the other hand, promotion and marketing, environment and regulations, and product image do not have a substantial impact on consumer decisions. Consumers are primarily drawn to the product because of its high quality, competitive price, dependable dealer network and services, and appealing credit schemes. However, limited marketing efforts and incomplete product information reduce awareness of the product's image and can hinder purchase interest. This leaves room for competitors who offer vehicles that are comparable to the product to capitalize on these weaknesses